First-principles study of the adsorption sensitivity of Ni-doped single-walled zigzag (n,0)CNTs (n=4,5,6) toward SO2 molecules - Li, Wei; Ma, Juan-Juan; Liu, Peng; Pan, Zhong-Liang; He, Qin-Yu (Applied surface science, 2015)
•The adsorption sensitivity of SWCNTs doped with Ni atom toward SO2 molecules was studied for the first time.•The adsorption capability of Ni-doped SWCNTs improved gradually with the increase of tube diameter in the small range.•Ni-doping decreased the primary symmetry of SWCNTs and the adsorption sensitivity was enhanced with the decrease of broken symmetry factor.•Ni-doped SWCNTs have much higher adsorption energy, larger net charge transfer values and shorter binding distances than pure SWCNTs because of chemisorption of the SO2 molecule. The adsorption of SO2 molecules on the surfaces of Ni-doped single-walled zigzag (n,0)CNTs (n=4,5,6, Ni-SWCNTs) has been investigated using density functional theory. The adsorption energies and changes in geometric and electronic structures after the adsorption were analyzed to characterize the sensitivity of Ni-SWCNTs toward SO2 molecules. Our calculated results showed that Ni-SWCNTs had much higher adsorption energy, larger net charge transfer values and shorter binding distances than pure SWCNTs owning to chemisorption of the SO2 molecule. The obtained density of states and frontier orbitals demonstrated that the orbital hybridization was obvious between the SO2 molecule and Ni-SWCNTs, while there was no evidence for hybridization between SO2 molecule and pure SWCNTs because of weak physisorption according to the total electron density maps. After doping of Ni atom, the primary symmetry of SWCNTs decreased, which enhanced the chemical activity of SWCNTs toward SO2 molecules consequently. Furthermore, the adsorption capability of Ni-SWCNTs was improved gradually with the increase of tube diameter in the small range. The above results have profound meaning for the design and fabrication of SO2 sensing devices.